2005
DOI: 10.1152/jn.00190.2005
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cingulate Cortical Neuronal Activity During Perception of Noxious Thermal Stimuli in Monkeys

Abstract: It has been reported that the anterior cingulate cortex (ACC) has a variety of functions relating to pain as well as pain perception. However, the underlying mechanisms for those functions remain unclear. To elucidate the functional role of the ACC in pain perception and pain-related functions such as attention to pain and escape from pain, single neuronal activity was recorded from the ACC, and the behavioral correlates of this neuronal activity was studied. A total of 667 neurons were recorded from the ACC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 55 publications
2
51
0
Order By: Relevance
“…47), and administration of noxious stimuli alone, such as hind paw formalin injections or footshock, as well as during training, induces c-Fos expression and increased ATP hydrolysis in the ACC (48,49). Studies of both monkeys and humans have shown that the ACC is activated by nociceptive stimuli as well as by the anticipation of pain (50)(51)(52). Recent findings indicate that the ACC is composed of at least two functionally distinct regions.…”
Section: Discussionmentioning
confidence: 99%
“…47), and administration of noxious stimuli alone, such as hind paw formalin injections or footshock, as well as during training, induces c-Fos expression and increased ATP hydrolysis in the ACC (48,49). Studies of both monkeys and humans have shown that the ACC is activated by nociceptive stimuli as well as by the anticipation of pain (50)(51)(52). Recent findings indicate that the ACC is composed of at least two functionally distinct regions.…”
Section: Discussionmentioning
confidence: 99%
“…Defining the role of ACC in pain Neurons in the ACC respond to both noxious and non-noxious mechanical or thermal somatosensory stimuli [38][39][40][41] . In particular, pyramidal neurons, which integrate inputs from the various cortical layers, are excited by noxious mechanical inputs 38,41 .…”
Section: Trace Fear Conditioningmentioning
confidence: 99%
“…In visceral pain models, electrical stimulation or microinjection of glutamate into the rostral ACC enhanced the visceromotor response to colorectal distension in normal rats while ACC lesions caused a decrease in the visceromotor response in viscerally hypersensitive rats but had no effect in normal rats [28] . Further study in monkey revealed that the ACC neurons are also involved in the anticipation that precedes the avoidance of aversive stimuli in one pain-avoidance task [29] and that ACC nociceptive neurons are involved in attention to pain and escape from pain but not in the sensory discriminative aspect of pain [30] . Distraction induced by a visual incongruent color-word Stroop task significantly reduced the visual analogue scale ratings for pain intensity and significantly increased the activation of the cingulo-frontal cortex, including the orbitofrontal and perigenual ACC as well as the PAG and the posterior thalamus [31] .…”
Section: Involvement Of Acc In Nociceptive Modulationmentioning
confidence: 99%